Biology of telomeres: lessons from budding yeast - Kupiec, Martin (FEMS microbiology reviews, 2014)
Abstract Telomeres are nucleoprotein structures that cap the ends of the linear eukaryotic chromosomes and thereby protect their stability and integrity. Telomeres play central roles in maintaining the genome's integrity, distinguishing between the natural chromosomal ends and unwanted double-stranded breaks. In addition, telomeres are replicated by a special reverse transcriptase called telomerase, in a complex mechanism that is coordinated with the genome's replication. Telomeres also play an important role in tethering the chromosomes to the nuclear envelope, thus helping in positioning the chromosomes within the nucleus. The special chromatin configuration of telomeres affects the expression of nearby genes; nonetheless, telomeres are transcribed, creating noncoding RNA molecules that hybridize to the chromosomal ends and seem to play regulatory roles. The yeast Saccharomyces cerevisiae, with its sophisticated genetics and molecular biology, has provided many fundamental concepts in telomere biology, which were later found to be conserved in all organisms. Here, we present an overview of all the aspects of telomere biology investigated in yeast, which continues to provide new insights into this complex and important subject, which has significant medical implications, especially in the fields of aging and cancer. Telomeres, the eukaryotic chromosomal ends, preserve genome stability and help duplicate the genome. They play important roles in aging and cancer. Here, we summarize our knowledge on the telomeres of the yeast Saccharomyces cerevisiae, a widely used model organism.